E-FOREX INDUSTRIJAS VIRZIENI UN ATTĪSTĪBAS PERSPEKTĪVAS - Fausts, Maksims (Latvijas Universitāte, 2007)
Introduction What moves the global FX industry? Is it controlled by large liquidity providers and institutions, or by traders in the market? To understand the interrelation between participators in the FX market it is significant to investigate certain factors that impact the market – spread, liquidity, as well as human and technological limitations. One-click trading is the key tool in FX trading today. Billions of one-click trades around the globe affect the fine model of FX global liquidity, simultaneously creating liquidity and testing its limits. Research about current situation in FX global industry and its participators is the key task of this work. More deeply will be considered electronic trading industry: its business model, substance of quotes and spreads, frequency of price update. Statistics and research such as human trader reaction and internet connection delays will be also presented. In response to these factors, a few practical recommendations are proposed for market participators who seek maximum trading efficiency in the managing and execution process. Specifically, how to deal with the high frequency of price updates and how to benefit from tighter spreads are examined. Possible future changes in FX market model will also be discussed. In an effort to provide its clients with deeper liquidity, the FX industry can adopt some changes to the current business model of FX Marketplaces in order to reach another level of integration. The theoretical concept of a global decentralized FX Marketplace is made real through the realization of multiple API connection technology. It is the difficulties and opportunities facing the industry in the challenge for liquidity which are the subject of this article. It will be also touched on the core technology and business model aspects involved in creating the global decentralized FX Marketplace network. The topic consists three main parts: 1.Evolutional process of the FX industry and its participators It describes history of foundation and main phases of FX market development from voice brokerage to electronic high technological market. There are mentioned main factors, which have influence on the FX business model. Also there are determined main market participators and their requirements from all aspects of business. 2.Regional FX industry development and perspectives In this chapter author is describing the most perspective areas from his point of view, which are still in a development process and becoming more and more attractive for investors. 3.Strategies and solutions for contemporary FX Industry The third chapter explains strategies and solutions used by biggest institutional market participators in order to offer competitive product, which is corresponds to clients expectations. Few researches will be presented regarding substance of liquidity, prices and the speed of execution. Finally will be given proposal, how to create a business model which is able to satisfy needs of every FX market participant and simultaneously will be able to hedge the own business risks. It is a hypothesis that in order to provide clients with deeper liquidity, the FX industry can adopt some changes to the current business model of FX Marketplaces in order to reach another level of integration. The theoretical concept of a global decentralized FX Marketplace is made real through the realization of multiple API connection technology. Author of this master thesis was being involved in research around main factors having influence on FX trading efficiency. Research was organized by Dukascopy SA (Swiss brokerage house), where author of this thesis is also working. The main target of this research was: “analyzing certain conditions, define optimal solution in realization of decentralized FX marketplace model”. Author has taken part of the research material and used it in master thesis.
DIRECTIONS AND DEVELOPMENT PROSPECTS FOR THE E-FOREX INDUSTRY
Keywords: Vadībzinātne